-7(3c-8)+(4(9+11c)=0

Simple and best practice solution for -7(3c-8)+(4(9+11c)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(3c-8)+(4(9+11c)=0 equation:



-7(3c-8)+(4(9+11c)=0
We add all the numbers together, and all the variables
-7(3c-8)+(4(11c+9)=0
We multiply parentheses
-21c+(4(11c+9)+56=0

See similar equations:

| x-36=22 | | 4(x-(2))=72 | | 6+z=-19 | | 10(x-5))=-80 | | 3x+7=(3x+7)-23 | | 17-6(2y-3)=0 | | 1/5=x/55000 | | -11x-27+19x=0 | | 230.000x+190.000=420.000 | | 230.000x+190.000=420.00 | | -418+x=1246 | | 0.75(x^2)=20 | | -7(7p-6)+8(6+4p)=0 | | 6/7x+8=26 | | -12x^2-3=0 | | (3x+1)²-2x=9x²+5 | | 42/x=x/21 | | y/2-20=-23 | | -48+x=-19 | | -2g+14=18 | | .5*(4+n)=12 | | 6/7=42/x | | 3​(x-5)=2​(x+5) | | -4b-11b=0 | | 6/27=34/x | | 4x(112)=24(56) | | -16+x=36 | | 8(x+5)=7(x+9) | | 13=9+2p | | 5(8x)=9(7x) | | n+2.5=6 | | -9x-(17-7x)=0 |

Equations solver categories